Ta có: 3x = 4y = 5z
\(\Rightarrow\frac{x}{\frac{1}{3}}=\frac{y}{\frac{1}{4}}=\frac{z}{\frac{1}{5}}=\frac{x-2y+3z}{\frac{1}{3}-\frac{1}{2}+\frac{3}{5}}=\frac{0}{\frac{13}{30}}=0\)
=> x = 0 x 1/3 = 0
y = 0 x 1/4 = 0
z = 0 x 1/5 = 0
Ta có: 3x = 4y = 5z
\(\Rightarrow\frac{x}{\frac{1}{3}}=\frac{y}{\frac{1}{4}}=\frac{z}{\frac{1}{5}}=\frac{x-2y+3z}{\frac{1}{3}-\frac{1}{2}+\frac{3}{5}}=\frac{0}{\frac{13}{30}}=0\)
=> x = 0 x 1/3 = 0
y = 0 x 1/4 = 0
z = 0 x 1/5 = 0
Tim x,y,z biet: a,(3x−2y)6+(y−5z)8+|z−2|=0(3x−2y)6+(y−5z)8+|z−2|=0
b,3x−2y4=2x−4z3=y−3z23x−2y4=2x−4z3=y−3z2va x+y+z=990
Gấp gấp gấp!
Tim x,y,z biet: a,(3x−2y)6+(y−5z)8+|z−2|=0(3x−2y)6+(y−5z)8+|z−2|=0
b,3x−2y4=2x−4z3=y−3z23x−2y4=2x−4z3=y−3z2va x+y+z=990
Gấp gấp gấp!
tim x y z biet
3x=4y=5z-3x-4y va 2x+y=z-38
tim x,y,z biet 3x=4y=5z va x+y+z=-94
Tim x,y,z biet:
\(\frac{5z-6y}{4}=\frac{6x-4z}{5}=\frac{4y-5x}{6}\) va 3x-2y+5z=96
Tim x,y,z biet (x-1)/2= (y+3)/4 =(z-5)/6 va 5z-3x-4y
tim x y z biết 3x=4y=5z-3x-4y và 2x+y=z-38
tim x y z biết 2x=3y=10z-2x-3yvà x+y=z-32
giải bài này giúp mk nha
Tìm x,y,z .Biết 3x = 2y , 4y = 5z và x+y-z = 78
Tìm x y z biết 3x=4y=5z và x+2y-3z=28
tim x, y , z biêt
5z-6y/4= 6x-4z/5= 4y-5x/6 và 3x -2y + 5z = 96